2009
DOI: 10.1071/mf08239
|View full text |Cite
|
Sign up to set email alerts
|

Infaunal macroinvertebrate assemblages of the eastern Great Australian Bight: effectiveness of a marine protected area in representing the region's benthic biodiversity

Abstract: Marine reserves are used widely throughout the world to conserve biodiversity, but in many instances uncertainties exist over how well these areas represent biodiversity at a regional scale (i.e. 100–1000 km). In the present study, infaunal assemblages were examined in the eastern Great Australian Bight (GAB) to evaluate the efficacy of the Benthic Protection Zone of the GAB Marine Park in representing regional biodiversity. Distributional patterns in infauna were further examined in relation to epifaunal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The second model included only a linear depth term and represented the positively linear hypothesis (H 2 ) (Escaravage et al 2009). The third model did not include depth and represented the hypothesis that richness was unrelated to depth (H 3 ) (Currie et al 2009). All models included percentage mud and very fine sand as additional covariates because we expected substrate to affect species richness in this region (Sanders 1968, Gray 1981, Karakassis and Eleftheriou 1997, Bergen et al 2001, Cosentino and Giacobbe 2008, Jayaraj et al 2008, Post 2008, Joydas and Damodaran 2009, Karenyi 2014.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The second model included only a linear depth term and represented the positively linear hypothesis (H 2 ) (Escaravage et al 2009). The third model did not include depth and represented the hypothesis that richness was unrelated to depth (H 3 ) (Currie et al 2009). All models included percentage mud and very fine sand as additional covariates because we expected substrate to affect species richness in this region (Sanders 1968, Gray 1981, Karakassis and Eleftheriou 1997, Bergen et al 2001, Cosentino and Giacobbe 2008, Jayaraj et al 2008, Post 2008, Joydas and Damodaran 2009, Karenyi 2014.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Macro-infaunal diversity most consistently relates to water depth as an environmental variable , Bergen et al 2001, Escaravage et al 2009); though correlates of water depth, including food availability, oxygen concentration and water movement, are likely responsible for observed diversity patterns (Snelgrove and Butman 1994). Three main macro-infaunal species richness-depth relationships have been described across continental shelves of different regions (Bergen et al 2001, Currie et al 2009, Escaravage et al 2009, Renaud et al 2009). Hypothesis 1 suggests a unimodal relationship between species richness and depth across the continental shelf with a peak in species richness at the middepths (Bergen et al 2001, Renaud et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currie et al (2009) and Ward et al (2006) reported on patterns of epifaunal and infaunal communities as related to environmental variables in the Great Australian Bight (GAB), one of the world's largest temperate carbonate shelfs. Ward et al (2006) reported on the results of the specimens collected with an epibenthic sled (1.8 m wide, 0.6 m high, 50 mm mesh bag), and Currie et al (2009) reported on the results of the specimens collected with a Smith-McIntyre grab, both of which were deployed on the same survey. For infaunal taxa, cluster analysis (using ANOSIM and BIO-ENV) resulted in three assemblages robustly correlated with depth (ρw=0.22).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases data from different gear types deployed on the same survey are reported in different scientific papers (e.g. Currie et al, 2009 andWard et al, 2006), creating difficulties identifying parallel datasets for comparison of equipment-specific results.…”
Section: Some Reasons For This May Includementioning
confidence: 99%